The Effect of NPF and ROA on Capital Buffer with CAR as a Moderating Variable in Indonesian Islamic Banking - Mujibno Mujibno; Luthfiyah Luthfiyah (al-Afkar, Journal For Islamic Studies, 2026)
Banks serve as financial intermediaries that connect parties with surplus funds to those in need of financing. The soundness of a bank is influenced by capital adequacy, which is measured through the Capital Adequacy Ratio (CAR). One key aspect in maintaining capital resilience is the capital buffer, which functions as a reserve to absorb financial risks. However, Islamic banking in Indonesia faces challenges such as high Non-Performing Financing (NPF) levels and low Return on Assets (ROA), both of which have the potential to erode the capital buffer and threaten financial stability. This phenomenon is evident in the case of PT Bank Muamalat Indonesia Tbk, which experienced a 37% decline in net profit in 2017 due to rising NPF and declining profit-sharing income. This study aims to analyze: (1) the effect of NPF on the capital buffer, (2) the effect of ROA on the capital buffer, and (3) the moderating role of CAR in the relationship between NPF and ROA on the capital buffer. This research utilizes secondary data from the financial reports of Islamic banks for the period 2015–2022. Data analysis was conducted using panel data regression and Moderated Regression Analysis (MRA). The results show that, partially, NPF has a negative and significant effect on the capital buffer, with a probability value of 0.013 (< 0.05), indicating that an increase in non-performing financing weakens the bank’s capital capacity. Conversely, ROA exhibits a negative but insignificant effect on the capital buffer, with a probability value of 0.098 (> 0.05), suggesting that profitability efficiency does not directly strengthen the bank's capital reserve. Moderation testing shows that CAR does not moderate the effect of either NPF or ROA on the capital buffer, as indicated by the interaction probability values of 0.9184 and 0.9237 respectively (> 0.05). These findings imply that credit risk and profitability management are more strongly influenced by the bank’s internal policies than by CAR as a structural moderating variable. Therefore, effective NPF management and profit utilization strategies should become key priorities in maintaining the capital stability of Islamic banks.